The Relationship of Religion to Tribal, Racial and Interfaith Conflicts - Husnul Khotimah; Indhra Musthofa (Islamic Extension Guidance Study Program (BPI) of the Faculty of Da'wah and Communication, 2023)
Abstrak: Keberadaan berbagai agama merupakan sunatullah yang telah ditetapkan oleh tuhan di bumi ini. Dengan adanya agama, manusia akan mendapat pandangan hidup yang akan mereka pegang seumur hidupnya. Dalam beragama, setiap masyarakat dipengaruhi oleh suku maupun budaya di masing masing daerah. Dalam pelaksanaanya, setiap agama saling mengadakan kontak sosial antar masyarakat baik itu positif maupun negatif. Dalam beragama, setiap umatnya akan mengembangkan dan menyeruh kepada masing masing pemeluk agamanya. Selain itu dalam setiap agama tentunya terdapat perintah untuk toleransi antar agama. Artikel ini ditulis dengan menggunakan metode kajian pustaka. Adanya pluralitas agama dan suku serta makin tingginya moderenitas horizontal bangsa Indonesia telah menimbulkan kontak kontak sosial budaya secara cepat dan meluas, termasuk kontak antar umat beragama. Akibat terjadinya kontak atau interaksi antar umat beragama tersebut kemudian dapat terjadi konflik ketika satu diantara kedua kelompok menganggap kelompok lain merugikannya, baik identitas maupun berbagai kebutuhannya. Persoalan persoalan pada level sosial-budaya antar kelompok agama maupun ditambah dengan persoalan politik sering melahirkan konflik antar umat beragama. Oleh karena itu, persoalan agama dalam masyarakat merupakan persoalan yang harus ditangani dan ditanggulangi dengan segera karena menyangkut penganut umat beragama agar tercipta kehidupan masyarakat yang damai dan hidup rukun selaras sesuai dengan yang dicita-citakan oleh setiap agama di seluruh dunia.Abstract: The existence of various religions is a sunatullah that has been established by God on this earth. With the existence of religion, humans will get a view of life that they will hold for the rest of their lives. In religion, every society is influenced by ethnicity and culture in each region. In its implementation, each religion establishes social contact between people, both positive and negative. In religion, every member of the community will develop and call upon each adherent of their religion. In addition, in every religion, of course, there is an order for tolerance between religions. This article was written using the literature review method. The existence of religious and ethnic plurality as well as the increasing horizontal modernity of the Indonesian nation has given rise to fast and widespread socio-cultural contacts, including contact between religious communities. As a result of contact or interaction between religious communities, conflict can then occur when one of the two groups considers the other group to be detrimental to them, both their identity and their various needs. Issues at the socio-cultural level between religious groups and coupled with political issues often give birth to conflicts between religious communities. Therefore, the issue of religion in society is a problem that must be addressed and dealt with immediately because it involves adherents of religious communities in order to create a peaceful society and live in harmony in accordance with what every religion in the world aspires to.